Design And Development Of A SEPIC Converter For PV Application - Omar, Rosli; Sulaiman, Marizan; Othman, Abdul Rani; Azri, Maaspaliza (UTeM, 2019)
The photovoltaics (PVs) are attractive sources of renewable energy for electric power generation due to their relatively small size and noiseless operation. The PV system exhibits a nonlinear i-v characteristics and its maximum power point varies with solar irradiation. The main purposes of this research are to design a Newton Raphson Technique as a controller based single-ended primary-inductor (SEPIC) converter of maximum power point tracking (MPPT). The developed controller will be applied to the SEPIC converter in order to track the MPPT. The proposed scheme based on its controller ensures optimal use of PV array and proves its efficacy in variable load conditions. The developed controller is then embedded with the real-time implementation of the MPPT SEPIC converter by using digital signal processor (DSP); TMS320F28335. The performance of the proposed SEPIC converter will be tested in both simulation and experiment at different operating conditions.